2019
DOI: 10.1177/2377960819887556
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and Pain in School-Aged Children and Adolescents: A Cross-Sectional Study

Abstract: Bullying is defined as repeated and unwanted aggressive behavior involving a power imbalance and hurt children and adolescents' socioemotional functioning. The aim is to investigate associations between pain (headache, stomach pain, backache, and neck/shoulder pain) and bullying among school-aged children and adolescents. This cross-sectional schoolbased survey comes from the Icelandic data set in the international research network Health Behaviour in School-Aged Children. The study population included all Ice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
7
0
2
Order By: Relevance
“…Bullying victimization is associated with health consequences including difficulty with sleep, poor eating habits, depression, and anxiety [ 19 , 20 , 21 , 22 ]. The prevalence of reported pain (e.g., stomachaches, headaches, and back pain) is significantly higher in victims of bullying [ 23 ]. Indeed, bullying victimization is recognized by the National Academies of Science, Engineering, and Medicine [ 24 ] as a serious health concern affecting children and adolescents worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Bullying victimization is associated with health consequences including difficulty with sleep, poor eating habits, depression, and anxiety [ 19 , 20 , 21 , 22 ]. The prevalence of reported pain (e.g., stomachaches, headaches, and back pain) is significantly higher in victims of bullying [ 23 ]. Indeed, bullying victimization is recognized by the National Academies of Science, Engineering, and Medicine [ 24 ] as a serious health concern affecting children and adolescents worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…The school nurse often sees children and adolescents with different types of pain such as headaches or stomach aches (Høie et al, 2017;Wigert et al, 2019). Physical pain is more common in children and adolescents who are also depressed (Borgman et al, 2020) or bullied (Garmy et al, 2019a). The use of painkillers is also more common in children and adolescents who are depressed (Hena et al, 2019) or bullied (Garmy et al, 2019b).…”
Section: Metaparadigm Of Nursing Theory-the Second Component In the Holistic Nursing Theorymentioning
confidence: 99%
“…Bullied children show worse social adjustment than other children (Goldbaum, Craig, Pepler, & Connolly, 2003), have lower self-esteem (Juvonen, Nishina, & Graham, 2000), and are more likely to be lonely and withdrawn and to internalise their problems (Goldbaum, Craig, Pepler, & Connolly, 2003). They are also more prone to various psychological and physical health problems (Garmy, Hansson, Vilhjálmsson, & Kristjánsdóttir, 2019a;Hansson, Garmy, Vilhjálmsson, & Kristjánsdóttir, 2020;Wright, 2015) as well as being at an increased risk of suicide attempts (Arnarsson, Malmquist, & Bjarnason, 2017). These symptoms are seen in victims of both sexes, all ages and irrespective of whether the bullying is direct or indirect, and such negative consequences of bullying are both reported by both the victims and their peers (Hawker & Boulton, 2000).…”
Section: Bullying and Place Avoidancementioning
confidence: 99%
“…On the contrary, an analysis of the international HBSC data revealed that bullying actually has a stronger negative effect on life satisfaction of individuals in schools and countries where bullying is less frequent (Arnarsson & Bjarnason, 2018). In Iceland, victims of bullying report poorer relations with their parents and are less likely to report having a best friend (Arnarsson & Bjarnason, 2009), report more physical and psychological symptoms (Garmy, Hansson, Vilhjálmsson, & Kristjánsdóttir, 2019a; Hansson, Garmy, Vilhjálmsson, & Kristjánsdóttir, 2020), use more pain medication controlling for self‐reported pain (Garmy, Hansson, Vilhjálmsson, & Kristjánsdóttir, 2019b), and are more likely to have attempted suicide (Arnarsson, Malmquist, & Bjarnason, 2017).…”
Section: Iceland As a Setting Of Studymentioning
confidence: 99%